Antiparasitic Behavior of Trifluoromethylated Pyrazole 2-Amino-1,3,4-thiadiazole Hybrids and Their Analogues: Synthesis and Structure-Activity Relationship - Camargo, Jeniffer do Nascimento Ascencio; Pianoski, Karlos Eduardo; dos Santos, Mariellen Guilherme; Lazarin-Bidóia, Danielle; Volpato, Hélito; Moura, Sidnei; Nakamura, Celso Vataru; Rosa, Fernanda Andreia (Frontiers in Pharmacology, 2020)
A series of trifluoromethylated pyrazole thiosemicarbazone, trifluromethylated pyrazole isothiosemicarbazone and trifluoromethylated pyrazole 2-amino-1,3,4-thiadiazole hybrids were synthesised and evaluated in vitro against the promastigote form of Leishmania amazonensis and the epimastigote form of Trypanosoma cruzi, the pathogens causing the neglected tropical diseases leishmaniasis and Chagas disease, respectively. The results show the potential of these compounds regarding their antiparasitic properties. Studies on the structure-activity relationship demonstrated that compounds containing a bulky group at the para position of the phenyl ring attached to the 5-position of the pyrazole core had better antiparasitic effects. Among the substituents attached at the 3-position of the pyrazole ring, the insertion of the 2-amino-1,3,4-thiadiazole nucleus led to the most potent compounds compared to the thiosemicarbazone derivative.